ChemInform Abstract: Iron‐Catalyzed C—H Borylation of Arenes. Issue 35 (September 2015) - Dombray, Thomas; Werncke, C. Gunnar; Jiang, Shi; Grellier, Mary; Vendier, Laure; Bontemps, Sebastien; Sortais, Jean‐Baptiste; Sabo‐Etienne, Sylviane; Darcel, Christophe
Abstract Both aromatic and heteroaromatic arenes undergo dehydrogenative borylation with pinacolborane catalyzed by a well‐defined iron bis(diphosphine) complexes under UV irradiation.